2023
DOI: 10.1111/hel.13033
|View full text |Cite
|
Sign up to set email alerts
|

The nonadherence and risk factors of eradication failure by sequential therapy as first‐line anti‐Helicobacter pylori treatment in real‐world clinical practice

Chun‐Te Lee,
Chung‐Tai Wu,
Wei‐Lun Chang
et al.

Abstract: BackgroundThe eradication rates of sequential therapy are high in clinical trials; however, the adherence for follow‐up or the patient population in a real‐world setting might be different from those in trails. This study investigates the effectiveness of sequential therapy in a real‐world setting and the factors that lead to treatment failure.Materials and MethodsIn this retrospective study, patients receiving sequential therapy as a first‐line anti‐Helicobacter pylori (H. pylori) treatment in a real‐world se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Female sex is a factor of eradication failure with concomitant therapy or sequential therapy, 25 but not of 10-day bismuth quadruple therapy. 7 , 8 , 9 In this study, sex-based analyses confirmed that the efficacy of 10-day bismuth quadruple therapy was non-inferior to that of 14-day therapy in male sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female sex is a factor of eradication failure with concomitant therapy or sequential therapy, 25 but not of 10-day bismuth quadruple therapy. 7 , 8 , 9 In this study, sex-based analyses confirmed that the efficacy of 10-day bismuth quadruple therapy was non-inferior to that of 14-day therapy in male sex.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, it requires a large-scale prospective multicentre study in different countries and regions or where the prevalence rate of metronidazole-resistance H. pylori is >40%. Second, the adherence to medications might be suboptimal in the real world 25 ; thus, the high efficacy for H. pylori treatment in a clinical trial may not be reflected in real-world practice. Third, considering multiple comparisons across adverse events, only the frequencies of dizziness but not vomiting were significantly different between the two groups after Bonferroni correction (Bonferroni corrected alpha level 0.0036).…”
Section: Discussionmentioning
confidence: 99%